Student Record Management for Administrative Service Quality at TK DYAS Montessori School - Moh. Irwan Hadi (LP2M STIT Palapa Nusantara, 2024)
Administrative service quality in early childhood education depends on the accuracy, accessibility, and security of student records. Although school administration has increasingly adopted digital tools, student record management in kindergarten institutions often remains fragmented across manual archives, simple digital files, and informal communication with parents. This study aims to analyze how student record management supports administrative service quality at TK DYAS Montessori School. A descriptive qualitative approach with a case study design was employed. Data were collected through observation, semi-structured interviews, and documentation involving the kindergarten principal, administrative staff, classroom teachers, and parents as supporting informants. Data were analyzed through data condensation, data display, and conclusion drawing, while credibility was strengthened through source, technique, and time triangulation. The findings indicate that student record management supports five administrative service functions: student registration, class administration, reporting, parent–school communication, and institutional documentation. However, the process still faces several constraints, including incomplete student documents, unscheduled data updating, uneven archive classification, partial integration between manual and digital records, and the absence of detailed written procedures. The school has attempted to improve student record management by completing documents, reorganizing archives, preparing digital recapitulations, strengthening coordination among school actors, and developing more standardized administrative procedures. This study concludes that student record management is not merely clerical work but a strategic administrative mechanism for improving service accuracy, work efficiency, data accountability, and institutional readiness in early childhood education. Theoretically, this study contributes to the literature on school administration and student data governance in kindergarten contexts. Practically, it provides implications for strengthening standardized, integrated, and accountable administrative services in early childhood education institutions.